State regulation and provision of safe transportation of dangerous freight in Ukraine - Лукьянов, С. Т.; Шарай, Г. В.; Шматков, В. Г.; Чернявский, И. А. (Proceedings of National Aviation University (archive), 2000)
Considered are the kinds of dangerous freight and provision of their safe transportation by air